THE ROLES OF ARTERIAL STIFFNESS AND BLOOD PRESSURE IN HYPERTENSION-ASSOCIATED COGNITIVE DECLINE IN HEALTHY ADULTS - Hajjar, Ihab (Hypertension, 2015)
Although there is strong evidence that hypertension leads to cognitive decline, especially in the executive domain, the relationship between blood pressure and cognition has been conflicted. Hypertension is characterized by blood pressure elevation and increased arterial stiffness. We aimed at investigating if arterial stiffness would be superior to blood pressure in predicting cognitive decline and explaining the hypertension-executive decline association. A randomly selected asymptomatic population (N=591, age=49.2 years, 70% women, 27% Black, education=18 years) underwent annual vascular and cognitive assessments. Cognition was assessed using computerized versions commonly used cognitive tests and principal component analysis was used for deriving cognitive scores for executive function, memory and working memory. Arterial stiffness was measured by carotid-femoral pulse wave velocity (PWV). Higher PWV, but not blood pressure, was associated with a steeper decline in executive (p=0.0002), memory (p=0.05) and working memory (p=0.02) scores after adjusting for demographics, education, and baseline cognitive performance. This remained true after adjusting for hypertension. Hypertension was associated with greater decline in executive score (p=0.0029) and those with combined hypertension and elevated PWV (>7 m/sec) had the greatest decline in executive score (p-value hypertension*PWV=0.02). PWV explained the association between hypertension and executive function (p-value for hypertension=0.0029 vs 0.24 when adjusting for PWV). In healthy adults, increased arterial stiffness is superior to blood pressure in predicting cognitive decline in all domains and in explaining the hypertension-executive function association. Arterial stiffness, especially in hypertension, may be a target in the prevention of cognitive decline.